Mobile Augmented Reality System for Emergency Response - Sharma, Sharad (IEEE, 2023)
There are a wide variety of mobile phone emergency response applications exist for both indoor and outdoor environments. However, outdoor applications mostly provide accident and navigation information to users, and indoor applications are limited to the unavailability of GPS positioning and WiFi access problems. This paper describes the proposed mobile augmented reality system (MARS) that allows both outdoor and indoor users to retrieve and manage information for emergency response and navigation that is spatially registered with the real world. The proposed MARS utilizes feature extraction for location sensing in indoor environments as during emergencies GPS and WiFi systems might not work. This paper describes the implementation of this MARS deployed on tablets and smartphones for building evacuation purposes. The MARS delivers critical evacuation information to smartphone users in the indoor environment and navigation information in the outdoor environments. A limited user study was conducted to test the effectiveness of the proposed MARS using the mobile phone usability questionnaire (MPUQ) framework. The results show that AR features were well integrated into the MARS and it will help identify the nearest exit in the building during the emergency evacuation.
2023 IEEE/ACIS 21st International Conference on Software Engineering Research, Management and Applications (SERA),May 23-25,2023,Orlando, FL, USA
Keywords: Indoor environment; Mars; mobile application; Sensors; Mobile augmented reality system; Augmented Reality emergency response; Buildings; two-dimensional/three-dimensional visualizations; Augmented reality; Navigation; evacuation; navigation; Emergency services